CP-168 Adding value: pharmacist interventions in ONCO-Haematological outpatients. (24th March 2015) - Escudero-Vilaplana, V; Ribed, A; Romero-Jiménez, RM; Buendía-Bravo, S; González-Haba, E; Codina, C; Herranz-Alonso, A; Sanjurjo Sáez, M
Abstract : Background: The continuing launch of new oral antineoplastic agents (OAAs) is changing the management of chemotherapy. Onco-haematological outpatients have acquired more autonomy and responsibility since OAAs require self-administration by patients at home. Therefore, hospital pharmacists are the latest health professionals in touch with patients and should detect the problems related to these drugs (DRPs). Purpose: To assess a pharmaceutical care program based on pharmacist interventions that aims to increase the effectiveness and safety of OAAs. Material and methods: The pharmaceutical care program, performed in November 2012, was evaluated in outpatients who started treatment with OAA during 2013. Pharmacist interventions took place during pharmacist interviews at the beginning of the treatment, after one and six months. Other variables were: demographics, ECOG, type of tumour, OAA and concurrent medicines. Results: 134 patients (mean age = 68.5 years old, 63.4% male) were included. 10.8% of patients had ECOG ≥ 1. Renal cancer (20.1%), prostate cancer (19.4%) and multiple myeloma (17.9%) were the most common tumours and the most frequent OAAs were abiraterone (20.1%) and lenalidomide (15.7%). On average, patients were taking 5 drugs concurrently. 362 pharmacist interventions were performed (84.3% with patients and 15.7% with doctors): 111 at the beginning of the treatment, 173 after the first month and 78 after six months. Interventions were classified as follows: 38.1% reinforcement of health education and literacy (management of side effects and improvement of healthy lifestyle); 30.4% drug-drug interactions (mainly with omeprazole and antihypertensives, 30.3% were type D or X according to the FDA); 9.9% correcting inappropriate drug administration; 6.1% dose modification; 3.8% adding, removing or substituting a drug and 11.7% others. The percentage of acceptance was 87.6% (range 62–100%). Conclusion: Pharmaceutical interventions and follow-up succeeded in detecting DRPs and improved the treatment of onco-haematological outpatients with high acceptance. The most frequent interventions consisted of improving the management of side effects and identifying drug interactions. References and/or Acknowledgements: No conflict of interest.